Bibliometric analysis of research trends in information seeking on social media - Komara, Diemas Arya; Rohman, Hasan Abdul; Rahmawaty, Alifia Putri; Giovanni, Farleynia; Mumtaz, Salsabila Raniyah (Comdent: Communication Student Journal, 2025)
Background: The rise of social media has transformed how individuals seek, process, and share information. However, the spread of misinformation and the challenge of low digital literacy present significant barriers to accurate information seeking. While previous research has focused on how information is disseminated, less attention has been given to how users actively search for reliable information on social media platforms. Purpose: This study aims to examine trends in information seeking on social media, focusing on the role of misinformation and digital literacy, while conducting a bibliometric analysis of the relevant literature. Methods:  A Systematic Literature Review (SLR) was combined with bibliometric analysis using Biblioshiny from the Bibliometrix R-package. Data were retrieved from the Scopus database, covering publications from 2020 to 2024, and a total of 627 articles were included after filtering. Results: The analysis identified the most influential publications, the most prolific authors, and dominant keywords. A co-occurrence network analysis was also conducted to map the connections among key concepts such as misinformation, digital literacy, anxiety, and information-seeking behavior. The findings reveal that misinformation remains a major challenge, especially during the COVID-19 pandemic, while digital literacy plays a significant role in shaping users’ information-seeking behavior. Notably, Dadaczynski, Hu, and Li emerged as the most productive authors, each contributing five publications. Prominent topics include infodemics, health literacy, and vaccine hesitancy. These findings highlight the importance of improving digital literacy and developing more effective communication strategies to navigate the evolving information ecosystem on social media.